Pengaruh Turnover Intention Dan Kompensasi Terhadap Tingkat Retensi Karyawan Pada Perusahaan Manufaktur Di Jawa Barat - Zahara Tussoleha Rony; Heri Fitriadi; Warkianto Widjaja (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2023)
This research investigates the influence of turnover intention and compensation on employee retention levels in manufacturing companies in West Java. A sample of 110 participants was recruited from various manufacturing companies in West Java. The research findings indicate that turnover intention and compensation significantly predict employee retention levels. Turnover intention has a significant negative impact on employee retention levels, while compensation has a significant positive impact on employee retention levels. These findings suggest that manufacturing companies in West Java need to address turnover intention issues and provide fair and competitive compensation packages to their employees if they want to improve employee retention levels. The findings of this research can assist manufacturing companies in West Java in developing effective strategies to enhance employee retention levels.